Predictors of psychosocial functioning among long- stay schizophrenia patients in a Malaysian mental institution - Teo, Pey Fang; Koh, Eugene Boon Yau; Chong, Seng Choi (Penerbit Universiti Sains Malaysia, 2024)
Background: A considerable number of schizophrenia patients still require long-term hospital care despite psychiatric deinstitutionalisation, especially in developing nations. Prolonged hospitalisation is associated with greater impairment in psychosocial functioning. This study aimed to determine the level of psychosocial functioning and its predictors among long-stay schizophrenia patients in a Malaysian mental institution. Methods: Our cross-sectional study included 138 patients selected through universal sampling. Data on socio-demographics, illness characteristics such as psychopathology and illness severity (measured using the Brief Psychiatric Rating Scale), and cognitive function (assessed using the Montreal Cognitive Assessment) were collected. The Personal and Social Performance (PSP) scale was used to evaluate psychosocial functioning. Pearson correlation coefficients and multiple linear regression analyses were applied to identify the correlates and predictors of psychosocial functioning. Results: Our study found that 47.8% and 16.7% of the patients had moderate and severe cognitive impairments, respectively. The mean PSP score was 69.68 (standard deviation (SD) = 15.48). Female gender, previous unemployment and more severe cognitive impairments were significantly associated with poorer psychosocial functioning. Meanwhile, negative symptoms and age of onset were negatively correlated with psychosocial functioning. By contrast, the duration of illness was positively correlated with psychosocial functioning. The regression model indicated that being female ( = -7.32, P < 0.001), previously unemployed ( = -3.67, P < 0.047), having negative symptoms ( = -4.18, P < 0.001), experiencing a longer illness duration ( = -0.60, P = 0.004) and the presence of severe cognitive impairment ( = -9.80, P < 0.001) significantly predicted poorer psychosocial functioning. Conclusion: Long-stay schizophrenia patients experience substantial difficulties in psychosocial functioning. Factors such as gender, last employment status, negative symptoms, illness duration and cognitive function affect psychosocial functioning.